2021
DOI: 10.1186/s13046-021-01926-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-dependent drivers of melanoma progression

Abstract: Hypoxia, a condition of low oxygen availability, is a hallmark of tumour microenvironment and promotes cancer progression and resistance to therapy. Many studies reported the essential role of hypoxia in regulating invasiveness, angiogenesis, vasculogenic mimicry and response to therapy in melanoma. Melanoma is an aggressive cancer originating from melanocytes located in the skin (cutaneous melanoma), in the uveal tract of the eye (uveal melanoma) or in mucosal membranes (mucosal melanoma). These three subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 326 publications
1
43
0
Order By: Relevance
“…However, HIF-1a was not restricted to hypoxic regions. As previously reported, the expression of HIF-1a in cells grown under normoxic conditions and in well-vascularized regions demonstrated the correlation of this protein, and more generally of its target genes, at the beginning of CM growth; when hypoxic areas are not yet obvious (29). After uveal melanoma cells were exposed to hypoxia, the expression and nuclear localization of HIF-1a increased, targeting VEGF genes, including VEGF-A, for its transcription (31,32).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, HIF-1a was not restricted to hypoxic regions. As previously reported, the expression of HIF-1a in cells grown under normoxic conditions and in well-vascularized regions demonstrated the correlation of this protein, and more generally of its target genes, at the beginning of CM growth; when hypoxic areas are not yet obvious (29). After uveal melanoma cells were exposed to hypoxia, the expression and nuclear localization of HIF-1a increased, targeting VEGF genes, including VEGF-A, for its transcription (31,32).…”
Section: Discussionsupporting
confidence: 73%
“…As reported for CM, hypoxia regulates the main signaling pathways involved in tumor progression and resistance to therapies. Many studies reported the essential role of hypoxia in regulating angiogenesis, VM, and response to therapy in melanoma ( 29 ). Hypoxia-inducible factors (HIFs), as a group of transcriptional activators, have emerged as the main regulators of these hypoxia-regulated angiogenic stimulators ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, cutaneous melanoma rates (the most aggressive skin tumor type) have continuously increased over the last two decades, and continue to increase. In the framework of OSA, in addition to the aforementioned epidemiological evidence, several studies using animal models to study melanoma tumor growth [ 14 , 15 ], metastasis [ 12 ] and potential interactions with obesity [ 16 ] confirmed that intermittent hypoxia mimicking the oscillations in oxygen tension that characterize OSA induce significant changes in the biological properties of melanoma cells, thereby promoting accelerated proliferation, invasion and resistance to therapy [ 12 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, it has also become apparent that there is considerable variability in the response to hypoxia by any type of malignant tumor, and that such heterogeneity may account for the conflicting findings in epidemiological studies attempting to link between OSA and cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma represents the most malignant type of skin cancer, with increasing incidence worldwide. Melanoma malignancy originates from pigment-producing melanocytes in the skin (cutaneous melanoma), in the choroid, ciliary body and iris of the eye (uveal melanoma) or in mucosal membranes from different sites (mucosal melanoma) [ 1 ]. Cutaneous melanoma (here referred simply as melanoma) is the most studied subtype among the three.…”
mentioning
confidence: 99%
“…Cutaneous melanoma (here referred simply as melanoma) is the most studied subtype among the three. Different predisposing factors to melanoma development have been reported, such as exposure to ultraviolet light radiation from sunlight, congenital and acquired melanocytic nevi, genetic susceptibility and family history [ 1 ]. As concerning somatic genetic alteration associated to melanoma, 40–50% of all melanoma patients harbor an activating BRAF mutation (mostly BRAF V600E), 20–30% NRAS mutations, 10–15% NF1 mutations and 1–3% KIT mutations [ 2 ].…”
mentioning
confidence: 99%